Fruit and vegetable consumption and lung cancer risk: updated information from the European Prospective Investigation into Cancer and Nutrition (EPIC). - Linseisen, J; Rohrmann, S; Miller, AB; Bueno-de-Mesquita, H; Büchner, F; Vineis, P; Agudo, A; Gram, I; Janson, L; Krogh, V; Overvad, K; Rasmuson, T; et al. (2007)
The association of fruit and vegetable consumption and lung cancer incidence was evaluated using the most recent data from the European Prospective Investigation into Cancer and Nutrition (EPIC), applying a refined statistical approach (calibration) to account for measurement error potentially introduced by using food frequency questionnaire data. Between 1992 and 2000, detailed information on diet and life-style of 478,590 individuals participating in EPIC was collected. During a median follow-up of 6.4 years, 1,126 lung cancer cases were observed. Multivariate Cox proportional hazard models were applied for statistical evaluation. In the whole study population, fruit consumption was significantly inversely associated with lung cancer risk while no association was found for vegetable consumption. In current smokers, however, lung cancer risk significantly decreased with higher vegetable consumption; this association became more pronounced after calibration, the hazard ratio (HR) being 0.78 (95% CI 0.62-0.98) per 100 g increase in daily vegetable consumption. In comparison, the HR per 100 g fruit was 0.92 (0.85-0.99) in the entire cohort and 0.90 (0.81-0.99) in smokers. Exclusion of cases diagnosed during the first 2 years of follow-up strengthened these associations, the HR being 0.71 (0.55-0.94) for vegetables (smokers) and 0.86 (0.78-0.95) for fruit (entire cohort). Cancer incidence decreased with higher consumption of apples and pears (entire cohort) as well as root vegetables (smokers). In addition to an overall inverse association with fruit intake, the results of this evaluation add evidence for a significant inverse association of vegetable consumption and lung cancer incidence in smokers.